2013
DOI: 10.1371/journal.pone.0080512
|View full text |Cite
|
Sign up to set email alerts
|

TAS2R38 and Its Influence on Smoking Behavior and Glucose Homeostasis in the German Sorbs

Abstract: BackgroundGenetic variants within the bitter taste receptor gene TAS2R38 are associated with sensitivity to bitter taste and are related to eating behavior in the Amish population. Sensitivity to bitter taste is further related to anthropometric traits in an genetically isolated Italian population. We tested whether the TAS2R38 variants (rs713598; rs1726866 and rs10246939) may be related to eating behavior, anthropometric parameters, metabolic traits and consumer goods intake in the German Sorbs.Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 21 publications
(54 reference statements)
8
55
0
Order By: Relevance
“…A few earlier studies examined the association between TAS2R38 diplotype and food and alcohol intake and smoking behaviour; however, the results are inconclusive173536. This inconsistent association between TAS2R38 diplotypes and dietary food intake might stem from the use of natural and artificial condiments in the study population17.…”
Section: Discussionmentioning
confidence: 94%
“…A few earlier studies examined the association between TAS2R38 diplotype and food and alcohol intake and smoking behaviour; however, the results are inconclusive173536. This inconsistent association between TAS2R38 diplotypes and dietary food intake might stem from the use of natural and artificial condiments in the study population17.…”
Section: Discussionmentioning
confidence: 94%
“…There are ϳ30 T2Rs expressed in humans. T2Rs are most abundant in the tongue, and T2R polymorphisms (e.g., T2R38) that impair the ability to taste bitter compounds have been correlated with populations that are more nicotine dependent and/or heavy smokers (80,97). Furthermore, when tongue tissue was compared for T2R mRNA expression in smokers vs. nonsmokers, overall T2R gene expression was reduced in the smoking compared with the nonsmoking group (8).…”
Section: Will Nicotine and Chemical Constituents In E-liquids/e-cigs mentioning
confidence: 99%
“…Variations in TAS2R43 affect bitter sensitivity to alloin and saccharin (23). Polymorphisms in TAS2Rs have also been analyzed in relation to dietary behavior, food and nutrient intakes, obesity or lifestyle-related diseases (24)(25)(26)(27)(28). Dotson et al reported that variation in TAS2R13 is associated with differences in alcohol consumption in cancer patients (26).…”
mentioning
confidence: 99%
“…Dotson et al reported that variation in TAS2R13 is associated with differences in alcohol consumption in cancer patients (26). Keller et al reported that PTC tasters for TAS2R38 tend to show lower alcohol and cigarette intakes (28). TAS2Rs are also known to be involved in non-gustatory physiology and pathology, including susceptibility to various diseases.…”
mentioning
confidence: 99%